The Sentiment Analysis Reviewing Indosat Services from Twitter Using the Naive Bayes Classifier - Febri Astiko; Achmad Khodar (Journal of Applied Computer Science and Technology, 2020)
This study aims to design a machine learning model of sentiment analysis on Indosat Ooredoo service reviews on social media twitter using the Naive Bayes algorithm as a classifier of positive and negative labels. This sentiment analysis uses machine learning to get patterns an model that can be used again to predict new data.